2014
DOI: 10.3109/07420528.2013.876428
|View full text |Cite
|
Sign up to set email alerts
|

Explaining why larks are future-oriented and owls are present-oriented: Self-control mediates the chronotype–time perspective relationships

Abstract: Recent studies provide evidence for the chronotype-time perspective relationships. Larks are more future-oriented and owls are more present-oriented. The present study expands this initial research by examining whether the associations are replicable with other time perspective measures, and whether self-control explains the observed relationships. Chronotype was assessed with the Morningness-Eveningness Questionnaire and the basic associations with the Zimbardo Time Perspective Inventory were replicated in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
49
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 46 publications
10
49
0
2
Order By: Relevance
“…In this study we investigated time perspective (specifically, future orientation) as another potential psychological mechanism mediating the relationship between chronotype and socio-sexuality. We replicated the association between morningness and future orientation already reported by previous studies (Díaz-Morales et al, 2008;Milfont & Schwarzenthal, 2014;Stolarski et al, 2013). Moreover, our mediation analyses revealed that the future orientation of morning-types was associated with their long-term mating orientation and relatively low sexual experience, while the present orientation of evening- (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study we investigated time perspective (specifically, future orientation) as another potential psychological mechanism mediating the relationship between chronotype and socio-sexuality. We replicated the association between morningness and future orientation already reported by previous studies (Díaz-Morales et al, 2008;Milfont & Schwarzenthal, 2014;Stolarski et al, 2013). Moreover, our mediation analyses revealed that the future orientation of morning-types was associated with their long-term mating orientation and relatively low sexual experience, while the present orientation of evening- (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Recent work also points to stable differences in executive function between early birds and night owls, which may explain their differences in time perspective. Specifically, a recent study by Milfont and Schwarzenthal (2014) showed that selfcontrol and ability to delay gratification are the mechanisms responsible for future-orientation in early birds, while deficiencies in these skills might account for the higher propensities for impulsivity and risktaking exhibited by evening-types (Caci et al, 2005;Killgore, 2007;Maestripieri, 2014). The hypothesis that there are chronotype-related differences in cognitive function is also consistent with evidence for differences in intelligence and in brain structure between early birds and night owls (Piffer, Ponzi, Sapienza, Zingales, & Maestripieri, 2014;Preckel, Lipnevich, Schneider, & Roberts, 2011;Rosenberg, Maximov, Reske, Grinberg, & Shah, 2014).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Future TP reflects a general orientation towards the future and has been linked with increased self-control and consideration of future consequences Milfont and Schwarzenthal 2014) which led directly to the hypothesis that (H8) future-oriented individuals would be more capable of controlling aggressive reactions. Theoretical analyses and empirical studies have shown that Future TP may enhance the positive consequences of Present Hedonism and attenuate the negative (e.g., Stolarski et al 2014).…”
Section: Time Perspective and Aggressionmentioning
confidence: 97%
“…Sin embargo, muchos estudios recientes cuestionan esta solución uni-factorial (Joireman et al, 2008;Petrocelli, 2003;Toepoel, 2010;Vásquez Echeverría, Esteves, Gomes, & Ortuño, 2015;ver, en cambio Hevey et al, 2010), sugiriendo una estructura de dos factores, donde el primero refleja la preferencia por las consecuencias inmediatas de las acciones (CFC-Inmediato) y el otro, las consecuencias más distantes (CFCFuturo). Esta división entre estos dos niveles de futuro, permite hacer un análisis más pormenorizado de los constructos estudiados y afinar la interpretación teórica de los datos (Joireman et al, 2012;Milfont & Schwarzenthal, 2014).…”
Section: Introductionunclassified